2016
DOI: 10.3389/fphys.2016.00047
|View full text |Cite
|
Sign up to set email alerts
|

Promising Therapy Candidates for Liver Fibrosis

Abstract: Liver fibrosis is a wound-healing process in response to repeated and chronic injury to hepatocytes and/or cholangiocytes. Ongoing hepatocyte apoptosis or necrosis lead to increase in ROS production and decrease in antioxidant activity, which recruits inflammatory cells from the blood and activate hepatic stellate cells (HSCs) changing to myofibroblasts. Injury to cholangiocytes also recruits inflammatory cells to the liver and activates portal fibroblasts in the portal area, which release molecules to activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 93 publications
1
54
0
Order By: Relevance
“…This study showed T1ρ MRI can differentiate BDL day-10 animals, when liver fibrosis (METAVIR stage-2) started to develop, from normal liver (33,34). Both animal experiments and clinical studies have revealed that liver fibrosis, even early cirrhosis, is reversible, treatment with combined therapies on underline etiology and fibrosis simultaneously might expedite the regression of liver fibrosis and promote liver regeneration (35)(36)(37).…”
Section: Bdl Is a Well Established Model For Liver Fibrosis Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…This study showed T1ρ MRI can differentiate BDL day-10 animals, when liver fibrosis (METAVIR stage-2) started to develop, from normal liver (33,34). Both animal experiments and clinical studies have revealed that liver fibrosis, even early cirrhosis, is reversible, treatment with combined therapies on underline etiology and fibrosis simultaneously might expedite the regression of liver fibrosis and promote liver regeneration (35)(36)(37).…”
Section: Bdl Is a Well Established Model For Liver Fibrosis Researchmentioning
confidence: 98%
“…Even when the underline etiology of liver fibrosis could not be eradicated, therapies on liver fibrosis might help restrict the disease progression to cirrhosis (37). Therefore early detection of liver fibrosis and treatment monitoring is of paramount importance.…”
Section: Bdl Is a Well Established Model For Liver Fibrosis Researchmentioning
confidence: 99%
“…ROS have been implicated in promoting fibrosis in multiple organs, such as the lung, liver, and kidney, through a number of mechanisms, as have been discussed in several recent reviews [160167]. Significantly, it has been established that ROS promote the transformation of fibroblasts to myofibroblasts by interacting with the TGF-β1 signaling pathway [168172]. ROS can augment the expression and secretion of TGF-β1 and activate the latent TGF-β1 to become active and functional.…”
Section: Rosmentioning
confidence: 99%
“…Hydrophobic bile acids are particularly toxic and promote cholangiocyte/hepatocyte damage, liver fibrosis, cirrhosis, and formation of hepatocellular carcinoma (HCC) under cholestatic conditions [13]. Deposition of collagen and other extracellular matrix components is an orchestrated event in cholestatic liver fibrosis and involves several cell types including Kupffer cells and stellate cells.…”
Section: Introductionmentioning
confidence: 99%